(untitled) (Conferencea, 2024)
The relevance of our work is due to the fact that at this time more and more new generation materials are being developed for teaching foreign languages to improve the quality of education and it is important for any teacher to know how to use visual, sound and technical teaching tools in order to effectively build work in the lesson for the highest possible result of mastering the material.